2014
DOI: 10.1128/jvi.00188-14
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Viral Replication and Modulated Innate Immune Responses in Infant Airway Epithelium following H1N1 Infection

Abstract: Influenza is the cause of significant morbidity and mortality in pediatric populations. The contribution of pulmonary host defense mechanisms to viral respiratory infection susceptibility in very young children is poorly understood. As a surrogate to compare mucosal immune responses of infant and adult lungs, rhesus monkey primary airway epithelial cell cultures were infected with pandemic influenza A/H1N1 virus in vitro. Virus replication, cytokine secretion, cell viability, and type I interferon (IFN) pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Furthermore, epithelial cells from juveniles housed in filtered air produced higher cytokine responses than those in conventional housing suggesting the microbial richness of the environment may influence epithelial responsiveness. The same group demonstrated that infant Rhesus monkey primary epithelial cell cultures are more permissive for the H1N1 influenza virus than those from adult airways, while producing less IL-1α (85). In humans, type I IFNs are detected at only low levels in the airways of RSV-bronchiolitic infants.…”
Section: Respiratory Epithelial Cellsmentioning
confidence: 99%
“…Furthermore, epithelial cells from juveniles housed in filtered air produced higher cytokine responses than those in conventional housing suggesting the microbial richness of the environment may influence epithelial responsiveness. The same group demonstrated that infant Rhesus monkey primary epithelial cell cultures are more permissive for the H1N1 influenza virus than those from adult airways, while producing less IL-1α (85). In humans, type I IFNs are detected at only low levels in the airways of RSV-bronchiolitic infants.…”
Section: Respiratory Epithelial Cellsmentioning
confidence: 99%
“…The group of incidence is similar to other significant respiratory pathogens in infants, such as RSV and PI viruses [32]. Accordingly, HBoV1 infection in very young children can relate to the immaturity of the innate immune response, which renders them more susceptible to respiratory infections during the first months of life [33,34]. The event of infection in newborns and young infants has been reported previously and raises questions concerning the presence of maternal antibodies with effective protection in this age group [10,24,35].…”
Section: Discussionmentioning
confidence: 74%
“…In an interesting study, Clay and colleagues modeled the susceptibility of human infants to severe influenza by experimentally infecting infant and adult rhesus macaques with the 2009 virus (Clay et al, 2014). Primary airway epithelial cultures from infant macaques supported higher levels of viral replication than cells from adults and displayed weaker innate immune responses.…”
Section: Experimental Infections Of Nhps With Human Influenza VImentioning
confidence: 99%